Why Distribution Losses are Still Uncontrollable?: A Case Study of Electricity Position in Haryana. - Setia, Lalit Kumar and Hawa Singh (2011)
This paper describes various factors affecting the electricity position in Haryana and explains the causes of uncontrollable distribution losses found after interviewing the Engineers and Administrative persons. The objectives were to disclose the socio, economic, technical, and political factors that influence the electricity distribution system in Haryana and to study the reasons behind persisting distribution losses, despite various initiatives such as 100% metering, replacement of old meters, accidental checks for reducing pilferage, and the Accelerated Power Development & Reform Programme (APDRP) programme, especially launched to reduce the losses. The government needs to think about improving the electricity position, reforming the power sector for meeting the increasing demands of consumers, and ensuring the 24-hours supply of electricity in order to support the economic growth of the State. The study gives directions to control the distribution losses by taking some critical administrative moves at the managerial level of Haryana Power Utilities